PELATIHAN PENGOLAHAN TEPUNG AMPAS KELAPA MENJADI BISKUIT DI DESA ADAT PENGLIPURAN, KABUPATEN BANGLI - Widarta, I W. R.; Suter, I K.; Yusa, N M.; Wiadnyani, A.A. I.S.; wati, NN. Puspa; Nocianitri, K. A. (Buletin Udayana Mengabdi; Vol 12 No 2 (2013): Jurnal Udayana Mengabdi, 2013)
Penglipuran village located on Bangli sub-district in Bangli regency. Coconut is one of agricultural commodities in this village. Rural community in Penglipuran village are inexperienced how to make cookies by coconut-by product. The aim of these activities was to introduce cookies production by coconut-by product to increase the added.value The Community Service was carried out by 2 methods, namely: first, information and discussion with rural community about cookies. Second, cookies production training. There are 20 partisipant in this activity, including delegation of female farmer groups. They have given positif response for these valuable activity.